Review: Pengaruh Nanopartikel ZnO sebagai Antimikroba pada Multidrug Resistance Klebsiella Pneumonia - Nuha Kudaer; Mohsen Hashim Risan; Emad Yousif; Mohammed Kadhom; Rasha Raheem; Nany Hairunisa; Husnun Amalia (Fakultas Kedokteran Universitas Trisakti, 2022)
Klebsiella pneumoniae (K. pneumoniae)is a common microorganism for different infections, including respiratory, urinary tract, and biliary diseases, where immunocompromised individuals are directly affected by this bacterium. However, with the emergence of hypervirulent strains, individuals,whether healthy or immunocompetent, are equally susceptible to K. pneumoniae infections. This problem is diagnosed by the wide spreading of multidrug-resistant bacteria in the environment with multiple resistance mechanisms, which are the main challenges for an effective treatment. This put physicians in an inflexible confusion because of the limitation of medical treatment options. Among many remedy substances, zinc oxide (ZnO) nanoparticles (NPs) showed remarkable antibacterial properties versus many Gram-positive and Gram-negative bacteria. This work focuses on presenting the influence of these NPs on the expression of genes in charged in generating the K. pneumoniae capsule. Furthermore, perspectives for applying ZnO NPs in clinical practices are also discussed. As the in vivo studies show a powerful impact of ZnO on bacteria, it is anticipated that this method of treatment will be utilized by hospitals.